2022
DOI: 10.3390/ijms23052801
|View full text |Cite
|
Sign up to set email alerts
|

Dickkopf-1 Promotes Angiogenesis and is a Biomarker for Hepatic Stem Cell-like Hepatocellular Carcinoma

Abstract: Cancer stemness evinces interest owing to the resulting malignancy and poor prognosis. We previously demonstrated that hepatic stem cell-like hepatocellular carcinoma (HpSC-HCC) is associated with high vascular invasion and poor prognosis. Dickkopf-1 (DKK-1), a Wnt signaling regulator, is highly expressed in HpSC-HCC. Here, we assessed the diagnostic and prognostic potential of serum DKK-1. Its levels were significantly higher in 391 patients with HCC compared with 205 patients with chronic liver disease. Rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 51 publications
2
11
0
Order By: Relevance
“…As a member of a typical carcinogenic signaling pathway, DKK1 plays an important anticancer role in human cancers [ 51 , 52 ]. Evidence has shown that DKK1 is not only involved in osteogenesis but also plays a central role in promoting tumor bone metastasis [ 53 , 54 ]. In the tumor tissue of thyroid papillary carcinoma (PTC), abnormal nuclear localization of β-catenin is associated with poor prognosis of PTC patients and thus contributes to tumor growth.…”
Section: Discussionmentioning
confidence: 99%
“…As a member of a typical carcinogenic signaling pathway, DKK1 plays an important anticancer role in human cancers [ 51 , 52 ]. Evidence has shown that DKK1 is not only involved in osteogenesis but also plays a central role in promoting tumor bone metastasis [ 53 , 54 ]. In the tumor tissue of thyroid papillary carcinoma (PTC), abnormal nuclear localization of β-catenin is associated with poor prognosis of PTC patients and thus contributes to tumor growth.…”
Section: Discussionmentioning
confidence: 99%
“…The most frequent mutations in HCC involve CTNNB1 (15.9–30%), AXIN1 (4.5–8%), and APC (0.8–3%) [ 263 , 283 , 340 ]. DKK1 is considered as an early-stage HCC biomarker [ 341 , 342 ], and CTNNB1 is enriched in proteomic subclass 3 [ 64 ]. CTNNB1 mutations are significantly associated with telomerase reverse-transcriptase promoter (TERT) mutations [ 343 ].…”
Section: Review Of Established and Novel Potential Targets In Hccmentioning
confidence: 99%
“…Additionally, activation of the Wnt signaling pathway reportedly controls the stemness of CSCs in different types of cancers including hepatocellular carcinoma (HCC), and colon, lung, and other cancers. [144][145][146][147][148] According to clinical practice, targeted treatment using MEKi (selumetinib, trametinib, and PD318088) inadvertently increased Wnt activity and led to enhanced stemness and tumor relapse in colorectal cancer. 149 Similarly, valproic acid, which was originally regarded as a histone deacetylase (HDAC) inhibitor in breast cancer treatment, can activate Wnt signaling pathway and promote the pool of mammary CSCs, leading to tumor progression.…”
Section: Epigenetic Mechanismsmentioning
confidence: 99%